Pers Mengawal Demokrasi Daerah: Analisis Pemberitaan Implementasi Dana Keistimewaan di Harian Tribun Jogja - Niti Bayu Indrakrista (Jurnal Ilmu Sosial dan Ilmu Politik, 2015)
This paper examines the role of local press as institution that supports democracy in regional level, indecentralisation era. As an entry point, this paper uses the media coverage of Dana Keistimewaan in TribunJogja daily newspaper, a non-partisan press institution that established at post New Order era. UsingRobert Entman’s framing analysis, this research argues that consolidation of democracy has not yet fullyembedded at regional level. Local presspays too many att ention on technocratic administrative aspects, rather than democratic ones that may involve contribution of the people.